Idiopathic carpal tunnel syndrome in male patients - Igor Sladojević; Tatjana Bućma; Ostoja Savić (Biomedicinska istraživanja, 2023)
Introduction. The carpal tunnel syndrome (CTS) in male patients, due to anatomical characteristics and the perception of CTS-related symptoms, remains undetected for a long time. Men respond less well to CTS treatment, and early detection enables conservative treatment of mild and moderate CTS. The aim of this paper was to examine the average age, the frequency of bilateral CTS and its correlation with the age, and to determine the grade of electrophysiological damage of the median nerve in male patients with idiopathic CTS diagnosed by electromyoneurography. Methods. The retrospective study included 83 male patients, aged from 32 to 81 years, with complaints of unilateral CTS on the right, dominant hand. All patients underwent EMNG for confirmation of CTS and the degree of median nerve damage. Statistical analysis was performed by methods of descriptive statistics, t-test, Wilcoxon signed rank test, and Pearson’s correlation coefficient. The value of p < 0.05 was considered statistically significant. Results. The average age of patients was 55.84 years. The bilateral CTS was confirmed in 88.4%, most often of a moderate degree and more pronounced on the right, dominant hand (p=0.001). In cases of bilateral CTS, age did not correlate with the grade of CTS changes in both hands. The changes in the dominant hand were more pronounced in patients older than 51 years. Conclusion. Male patients with idiopathic CTS usually have bilateral CTS, with more pronounced changes on dominant hand. Bilaterality of CTS and the degree of median nerve damage are not connected with age.